Báo cáo tổng hợp ý kiến, kiến nghị của cử tri và Nhân dân (Tại kỳ họp thứ hai, Quốc hội khóa XV) (Số: 408/BC-MTTW-ĐCT) - Đoàn Chủ tịch UBTWMTTQ Việt Nam (2021)
Toàn văn Báo cáo tổng hợp ý kiến, kiến nghị của cử tri và Nhân dân (Tại kỳ họp thứ hai, Quốc hội khóa XV) (Số: 408/BC-MTTW-ĐCT)